Grants versus Loans for Development Banks - Bulow, Jeremy; Rogoff, Kenneth (American Economic Review, 2005)
In recent years, economists have increasingly debated whether multilateral development banks, such as the World Bank, should switch from making subsidized loans to giving outright grants. It is no small question. The combined loans of the World Bank Group and brethren regional entities such as the Asian and Inter-American Development Banks, approach $300 billion. Their funds constitute a main channel through which rich country governments provide assistance to developing country governments. In Bulow and Rogoff (1990), we first developed the case for a shift to outright grants. We argued that under the status quo, a vastly disproportionate share of aid goes to middle income countries via disguised interest subsidies, rather than to the poorest countries. We also argued that a shift to grants would protect donor banks from sometimes having to play a “bad cop” role when trying to collect net repayments rather than fully rolling over loans. The “Meltzer Commission” (International Financial Institution Advisory Commission, 2000) report on government sponsored international lending institutions famously took a similar view. Supporters of the status quo often argue that development bank loans to middle income countries are in fact highly profitable, and are essential for allowing institutions like the World Bank to subsidize aid to poor countries. We shall argue that the Bank’s profitability is an accounting artifice that greatly underestimates the risks of the Bank’s portfolio. Another argument for loans is that multilateral development banks have a superior enforcement technology that helps international debt markets to function more efficiently. Thus loans allow financially strapped governments, including in middle-income countries, to borrow more than they could otherwise. We will argue that this benefit, too, is an illusion. In those cases when official lending does expand a developing country government’s borrowing capacity, it effectively enables the government to commit the country to repayment levels beyond that supported by domestic political consensus, creating moral hazard for shortsighted rulers. In theory, better credit access to finance, say, public infrastructure projects can be highly beneficial. In practice, however, the increased risk of debt crisis all too often outweighs any gain ordinary citizens might enjoy from the loans. Furthermore, moral hazard on the part of lenders, who may be able to induce rich countries into subsidizing the bailout of troubled middle-income borrowers, may mean that aggregate lending is excessive even if multilaterals merely displace equivalent private debt. We do not argue for eliminating assistance to middle-income countries. On the contrary, we would favor expanding aid in general, albeit in far greater proportion to the world’s poorest countries. Note that in principle, any country with market access could use grant flows to help defray interest rate costs on loans if it so chose, but development banks would never need to assume a “bad cop” role in enforcing debt.